Phytochemical and Wound Healing Effects of Methanolic Extract of Salvia multicaulis Vahl. in Rat - I Salimikia; M Aryanpour; R Bahramsoltani; M Abdollahi; AH Abdolghaffari; N Samadi; F Sabbaghziarani; M Gholami; HR (Institue of Medicinal Plants, ACECR, 2016)
Background: Plants and their phytochemicals have immense potential for the management of different types of wound. Salvia multicaulis Vahl. is an evergreen shrub species, which traditionally used as a wound healing agent. Objective: The aim of the present study is to evaluate phytochemicals and wound healing activity of S. multicaulis in an excision wound model. Methods: Preliminary phytochemical screening tests were performed on the methanol (80%) extract. Total phenolic content was measured using Folin-Ciocalteu reagent. Antioxidant activity of the extract was assessed by (DPPH) free radical scavenging test. 2x2 excision wounds were induced in the dorsal area of 30 Wistar rats. Animals were received topical eucerine, 1% phenytoin as well as 5%, 10% and 20% ointments of the plant extract in eucerine base. Wound areas were photographed and wound contraction was calculated as the reduction percentage of wound size compared with zero days. Last day skin samples of wounded area were used for histological evaluations. Results: Collagen deposition for positive control group and A20% were low fibrils and A10% high fibrils and A5% highest fibrils. Total phenolic content was 262.083 ± 47.15 mg GAE/g extract. IC50 was 54.02 µg/mL. All concentrations of the extract ointments were significantly effective in the animal model of excision wound (P<0.05) which was also confirmed in histological study. Conclusion: It is concluded that S. multicaulis extract could act as a wound healing agent. This activity is possibly due the high concentrations of phenolic compounds.